The Impact of Dietary Factors on Glycemic Control, Insulin Sensitivity and Secretion in the First Years after Diagnosis of Diabetes - Weber, K. S.; Buyken, A. E.; Nowotny, B.; Strassburger, K.; Simon, M.-C.; Pacini, G.; Szendroedi, J.; Müssig, K.; Roden, M.; for the GDS Group (Experimental and Clinical Endocrinology & Diabetes, 2016)
Background: Dietary factors play an important role in the prevention of diabetes mellitus. We tested the hypothesis that dietary factors related to diabetes onset also associate with its progression, i. e., early time courses of insulin sensitivity and secretion in both type 1 and type 2 diabetes.Methods: In a prospective observational study, well-controlled recent-onset diabetes patients (n=127) underwent detailed metabolic characterization within the first year after diagnosis. A follow-up was conducted 2 years after the first examination. Insulin secretion and sensitivity were assessed by intravenous glucose tolerance testing. Baseline food consumption was analyzed by a food propensity questionnaire. Multivariate linear regression analysis was used to assess associations between consumption frequencies at baseline with metabolic changes during the first 2 years.Results: Within the first 2 years, metabolic control did not change in patients with type 1 and type 2 diabetes on average. In type 1 diabetes, an increased consumption frequency of refined grains by one time/day at baseline associated with higher HbA1c by 0.60% (95% CI: 0.04; 1.16), P=0.04 after 2 years compared to baseline. In type 2 diabetes, an increased consumption frequency of meat/meat products by one time/day at baseline associated with lower beta-cell adaptation index (−7.25% (95% CI: −13.16; −0.93), P=0.03) after adjustment for age, sex, BMI, and changes of BMI and glucose-lowering medication.Conclusion: Dietary factors associate with the initial course of diabetes. Reduced consumption of refined grains in type 1 diabetes and of meat products in type 2 diabetes may contribute to preservation of insulin secretion and sensitivity.
Keywords: insulin resistance; beta-cell function; HbA1c; lifestyle